Adaptive Reuse of Heritage Buildings in Cultural Tourism: A Multi-Layered Design-Tourism Interface Framework from Kota Lama Surabaya - Daniel Pandu Mau; Freddy Hendrawan; Ramanda Dimas Surya Dinata (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
Historic urban heritage areas are key resources for cultural tourism but often face challenges of functional obsolescence and underutilization. Existing studies, however, often examine adaptive reuse from architectural or tourism perspectives separately, with limited integration between these dimensions. This study examined how design-based adaptive reuse of heritage buildings contributes to cultural tourism development in Kota Lama Surabaya by analyzing functional repositioning, design mediation, and tourism value structuring as interconnected processes shaping tourism outcomes. A qualitative multi-case study approach was employed, focusing on four heritage buildings representing different cultural zones. Data were collected through field observations, in-depth interviews, and document analysis, and analyzed using within-case and cross-case comparative methods. The findings reveal that adaptive reuse operates as an integrated interaction-based system rather than a linear transformation. Functional repositioning redefines the role of heritage buildings within socio-economic and tourism systems, while design mediation translates these changes into spatial experiences and cultural narratives. Tourism value emerges through the interplay of economic, experiential, and symbolic dimensions, which are often characterized by inherent tensions. This study proposes a multi-layered design-tourism interface framework, demonstrating that the effectiveness of adaptive reuse depends on the alignment between function, design, and value. Through integrating design and tourism perspectives, the study contributes to adaptive reuse literature by conceptualizing heritage transformation as an interconnected socio-spatial and experiential process within tourism systems.